Crop Water Productivity: Within-Field Spatial Variation in Irrigated Alfalfa (Medicago sativa L.) - Keegan Hammond; Ruth Kerry; Ross Spackman; April Hulet; Bryan G. Hopkins; Matt A. Yost; Neil C. Hansen (AgriEngineering)
In this study, alfalfa (Medicago sativa L.) is evaluated for suitability of variable rate irrigation (VRI) by analyzing within-field variation in crop water productivity (CWP) under uniform irrigation. The objectives were to (1) measure within-field variation in crop evapotranspiration (ET), (2) quantify spatial variability of alfalfa biomass yield, and (3) assess whether a bivariate analysis of CWP and yield could inform VRI management zones. Research was conducted on a 22.6 ha center-pivot irrigated alfalfa field near Rexburg, Idaho, USA, over three harvest intervals (HIs) in 2021 and 2022. Using a water balance method at 66 field points, ET exhibited significant spatial clustering for each HI (p < 0.001 for all HIs), though spatial patterns varied among HIs. Biomass yield, measured via the quadrat method, ranged from 2.1 to 9.7 Mg ha−1, with significant spatial clustering (p < 0.001 for all HIs). The CWP ranged from 0.07 to 0.54 Mg ha−1 cm−1, also showing significant spatial clustering (p < 0.001 for all HIs). Bivariate cluster analysis indicated 12–18% more area of the field was over-watered than under-watered, suggesting potential for optimizing irrigation with VRI. Reducing irrigation in these over-watered zones could improve CWP, supporting alfalfa as a viable candidate for VRI.